Estradiol-17β hormone concentration and follicles number in exotic Burgo chicken supplemented by Sauropus androgynus leaves extract - HERI DWI PUTRANTO; JOHAN SETIANTO; URIP SANTOSO; WARNOTO WARNOTO; NURMELIASARI NURMELIASARI; AHMAD ZUENI (Biodiversitas Journal of Biological Diversity, 2012)
Putranto HD, Setianto J, Santoso U, Warnoto, Nurmeliasari, Zueni A. 2012. Estradiol-17β hormone concentration andfollicles number in exotic Burgo chicken supplemented by Sauropus androgynus leaves extract. Biodiversitas 13: 1-6. Bengkulu Province of Indonesia has an indigenous crossbreed chicken named burgo or Rejang chicken. A conservation effort in this study was represented by supplementing 4 different levels of Sauropus androgynus or katuk leaves extract (KLE) to improve number of fertile eggs. The purpose of study was to identify the effects of KLE supplementation on female burgo chicken’s serum estradiol-17β (E2) hormone concentration profile and number of follicles. KLE was added into drinking water (0, 9, 18 and 27 g/chicken/day) during 8 weeks of treatment. The results showed that supplementation of KLE dosed 9 to 27 g/chickens/day had significantly affected E2concentrations and number of follicles (P < 0.05). In contrast, the average of female burgo E2 concentration with supplemented KLE was higher than control group. The total number of small follicle yield was highest (86.5%) compared to medium follicle (7.8%) and large follicle (5.3%). Many primary follicles (primordial) and post ovulatory follicles were probably in micro size and unseen by an usual visual counting. It seems that serum E2 hormone concentration correlated to total number of preheararchal follicles. Supplemented KLE was able to improve the serum estrogen steroid hormone concentration and number of preheararchal follicle (small and medium follicles) in female burgo chicken.